The core components of organelle biogenesis and membrane transport in the hydrogenosomes of Trichomonas vaginalis - Rada, Petr; Doležal, Pavel; Jedelský, Petr L; Bursac, Dejan; Perry, Andrew J; Šedinová, Miroslava; Smíšková, Kateřina; Novotný, Marian; Beltrán, Neritza Campo; Hrdý, Ivan; Lithgow, Trevor; Tachezy, Jan (PloS one, 2011)
Trichomonas vaginalis is a parasitic protist of the Excavata group. It contains an anaerobic form of mitochondria called hydrogenosomes, which produce hydrogen and ATP; the majority of mitochondrial pathways and the organellar genome were lost during the mitochondrion-to-hydrogenosome transition. Consequently, all hydrogenosomal proteins are encoded in the nucleus and imported into the organelles. However, little is known about the membrane machineries required for biogenesis of the organelle and metabolite exchange. Using a combination of mass spectrometry, immunofluorescence microscopy, in vitro import assays and reverse genetics, we characterized the membrane proteins of the hydrogenosome. We identified components of the outer membrane (TOM) and inner membrane (TIM) protein translocases include multiple paralogs of the core Tom40-type porins and Tim17/22/23 channel proteins, respectively, and uniquely modified small Tim chaperones. The inner membrane proteins TvTim17/22/23-1 and Pam18 were shown to possess conserved information for targeting to mitochondrial inner membranes, but too divergent in sequence to support the growth of yeast strains lacking Tim17, Tim22, Tim23 or Pam18. Full complementation was seen only when the J-domain of hydrogenosomal Pam18 was fused with N-terminal region and transmembrane segment of the yeast homolog. Candidates for metabolite exchange across the outer membrane were identified including multiple isoforms of the β-barrel proteins, Hmp35 and Hmp36; inner membrane MCF-type metabolite carriers were limited to five homologs of the ATP/ADP carrier, Hmp31. Lastly, hydrogenosomes possess a pathway for the assembly of C-tail-anchored proteins into their outer membrane with several new tail-anchored proteins being identified. These results show that hydrogenosomes and mitochondria share common core membrane components required for protein import and metabolite exchange; however, they also reveal remarkable differences that reflect the functional adaptation of hydrogenosomes to anaerobic conditions and the peculiar evolutionary history of the Excavata group.
Keywords: Mitochondria; mitochondrie; membránové proteiny; Membrane Proteins; Sequence Homology, Amino Acid; molekulární sekvence - údaje; Amino Acid Sequence; protozoální proteiny; Chromatography, Gel; poriny; sekvenční homologie aminokyselin; elektroforéza v polyakrylamidovém gelu; organely; Trichomonas vaginalis; biologický transport; Electrophoresis, Polyacrylamide Gel; Organelles; Porins; gelová chromatografie; sekvence aminokyselin; Molecular Sequence Data; Protozoan Proteins; Biological Transport